Dynamic Analysis Evaluation and Control of A Full Vehicle Suspension System - Mohammed Khaled Akel; Ali Ahmed, Abdssalam; Taher Abdallah Ali Galouz; Abdulrauf Salheen Alatrash (African Journal of Advanced Pure and Applied Sciences, 2023)
In this paper, a full car active suspension system is to be developed as a mathematical model and introduce its kinematics. A state space representation is extracted and used as the basis for the Simulink model, through which the controllers are to be designed. This model focuses on the vertical motion of the vehicle's suspension system and a displacement pulse is used to represent a real-life road pump for the disturbance signal, with the goal is to attenuating and minimize its effect to produce the most likely smooth state trajectories with a short time to recover, thus a comfortable ride for the passengers is to be achieved. Two controllers are designed in this work splitting into two types, linear and non-linear control methods. A PID controller is the linear part and a Fuzzy PID controller is chosen as a nonlinear controller. Both of these controllers are to be introduced to the system, tuned and refined to get the best possible response, a comparison is then made to see each controller's advantages and benefits.